Pengembangan Hasil Belajar Siswa Melalui Penerapan Model Problem Based Learning Integrasi Media Monopoli - Isro'ullaili; Edy Herianto; Sawaludin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2023)
This study aims to determine whether there is an effect of applying the Problem Based Learning model assisted by monopoly media on student learning outcomes in class VIII PPKn subjects at SMPN 1 Mataram. The approach used is quantitative with the type of research Quasi Experimental Design with the type of Nonequivalent Control Group Design. The population in this study were all 11 graders of class VIII SMPN 1 Mataram. The sample in this study was taken using a purposive sampling technique. So from the 11 classes two classes will be taken as research samples, namely class VIII G (experimental class) and class VIII J (control class). Data collection was carried out by observation and test techniques. The instrument used is a multiple choice test. The test technique used is the pre-test and post-test. The analysis prerequisite test used for the normality test is the Chi Square Test and the homogeneity test uses the Variance Test. To test the hypothesis using the t-test. The results of the study used the t-test at a significance level of 5% where tcount > ttable (4,135 > 1,994) was obtained so that the conclusion was that Ha was accepted and Ho was rejected, meaning that there was an influence of the Media Monopoly Assisted Problem Based Learning Model on Student Learning Outcomes in Civics Subjects at SMPN 1 Mataram.